# What is the answer for question 4.a)? (Draw 2) http://postimg.org/image/q8ectggh3/

*print*Print*list*Cite

### 1 Answer

The picture represents a parabola that opens upward, hence a>0, whose vertex (h,k) is at (3,-7), hence, you may write the equation of the corresponding quadratic function, such that:

`f(x) = a(x - h)^2 + k`

Considering a = 1 yields:

`f(x) = (x - 3)^2 - 7`

You need to represent the graph of transformed function `y = f(x - 3) + 5` , based on the graph of original function, such that:

- move vertically the red graph up 5 units: `y = f(x) + 5 => y = (x - 3)^2 - 7 + 5 => y = (x - 3)^2 - 2`

- shift the graph 3 units to the right, such that: `y = (x - 3 - 3)^2 - 2 => y = (x - 6)^2 - 2`

**Hence, sketching the graph of transformed function `y = f(x - 3) + 5 = (x - 6)^2 - 2 ` yields:**